Range-Dependent Variance Correction Method for High-Resolution and Wide-Swath Spaceborne Synthetic Aperture Radar Imaging Based on Block Processing in Range Dimension - Zhenyu Hou; Zehua Zhang; Pin Li; Zhuo Yun; Feng He; Zhen Dong (Remote Sensing)
With increasing demands for SAR image applications, spaceborne SAR systems are evolving towards higher resolution and wider swath capabilities. However, these advancements lead to more pronounced range-dependent variance effects. Previous research has primarily focused on the impact of range-dependent variance on range cell migration and the quadratic phase of range frequency, while often neglecting the effects of the cubic phase of range frequency. Although some block processing methods have addressed the range-dependent variant cubic phase of range frequency, they lack detailed impact analyses and segmentation criteria. This paper first proposes a Circle–Sphere geometric model to establish a theoretical framework for analyzing range-dependent variance impacts. Through simulation experiments, we validate the theoretical model’s accuracy and develop a numerical analysis of range-dependent variance effects. Building upon this foundation, we introduce a range-dependent variance correction method based on block processing in the range dimension. This method, incorporating valid data area and buffered data area, effectively corrects range-dependent variance while preventing data wrapping and fragmentation. Moreover, our theoretical model for analyzing range-dependent variance impacts provides both theoretical and numerical foundations for block segmentation criteria. The effectiveness and applicability of the proposed method are validated through both simulation experiments and real data experiments using GF3.